PENGARUH SARANA PRASARANA SEKOLAH TERHADAP MINAT DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VIII SMP NEGERI 10 PEMATANG SIANTAR TAHUN AJARAN 2022/2023. - Sihombing, Samuel Marlas Roha; Sihombing, Sotarduga; Siagian, Lasma (Penerbit Widina, Widina Media Utama, 2023)
The aim of this research is to see the extent of the influence of school infrastructure on students' interest and learning achievement in the Integrated Social Sciences Subjects for Class VIII at SMP Negeri 10 Pematang Siantar for the 2022/2023 academic year.